Regulation of Circadian Behavioral Output via a MicroRNA-JAK/STAT Circuit. - Luo, W.; Sehgal, A. (Cell, 2012)
Although molecular components of the circadian clock are known, mechanisms that transmit signals from the clock and produce rhythmic behavior are poorly understood. We find that the microRNA miR-279 regulates the JAK/STAT pathway to drive rest:activity rhythms in Drosophila. Overexpression of microRNA miR-279 or miR-279 deletion attenuates rest:activity rhythms. Oscillations of the clock protein PERIOD are normal in pacemaker neurons lacking miR-279, suggesting that miR-279 acts downstream of the clock. We identify the JAK/STAT ligand, Upd, as a target of miR-279 and show that knockdown of Upd rescues the behavioral phenotype of miR-279 mutants. Manipulations of the JAK/STAT pathway also disrupt circadian rhythms. In addition, central clock neurons project in the vicinity of Upd-expressing neurons, providing a possible physical connection by which the central clock could regulate JAK/STAT signaling to control rest:activity rhythms.